SAYYANG PATTUDU TRADITION: HOW IT IMPLIES TO SOCIETY SOCIO-ECONOMICS - Ratnah Ratnah (Tasharruf: Journal Economics and Business of Islam, 2020)
The Sayyang pattu’du 'tradition was held at the moment to commemorate the birthday of the Prophet Muhammad. Usually followed by tens of more participants in the village of Lero, among the participants in the village of Lero there are also those who come from the village or neighboring village of Ujung Labuang village. The implementation of this activity is usually held en masse in the village of Lero but sometimes there are those who do it themselves outside of the Prophet's Birthday as in marriages. A qualitative method with a social approach was adopted in completing this research. This tradition has economic implications for the Lero community in carrying out the Sayyang pattu’du tradition, namely the people who carry out the tradition can carry out consumption activities, namely renting various Sayyang pattu’du traditional equipment, including horses, mustard (horse handlers), parrawana, pesarung (companions), pakkalinda'da ', Mandar and badawara traditional clothes (clothes for children who share the Qur'an) and can buy food ingredients to make food that is served to guests who come, wherein the rental there are some people who rent all the equipment and there are also people who do not rent all the equipment.